Efficacy and Safety of Evolocumab in Improving Low-Density Lipoprotein Cholesterol (LDL-C) Levels in a Japanese Population ― Systematic Review and Meta-Analysis - Sheng, Feng; Miyawaki, Kazuma; Osada, Nobuhiro; Tanaka, Satoru; Liu, Zhaoyuan; Shinke, Toshiro (Circulation Reports, 2025)
Background: Hypercholesterolemia is a major risk factor for cardiovascular disorders. Evolocumab is efficacious and safe for the management of low-density lipoprotein cholesterol (LDL-C); however, evidence supporting the utility of evolocumab in Japanese patients is lacking. To fill this evidence gap, we conducted this systematic review and meta-analysis.Methods and Results: PubMed, EMBASE, Web of Science, and the Cochrane Library from inception to October 2023 were searched for relevant publications. The primary outcomes were LDL-C levels and coronary artery plaque regression or stabilization. The secondary outcome was the incidence of adverse events. Nine studies were included: 6 randomized control trials (RCTs) and 3 cohort studies. The meta-analysis showed that evolocumab significantly reduced LDL-C levels in RCTs in the short (≤1 month), medium (≤3 months), and long (1 year) term, with a mean difference (MD) relative to placebo/standard of care (SOC) of −52.06% (95% confidence interval [CI] −59.32%, −44.79%), −69.12% (95% CI −71.45%, −66.79%), and −78.08% (95% CI −82.98%, −73.18%), respectively, and in the mid- to long (≤6 months) term in a cohort study, with an MD of −57.81% (95% CI −74.37%, −41.25%). Evolocumab also increased fibrous cap thickness and reduced macrophage grade. Adverse events were rare across included studies.Conclusions: Evolocumab seems to be effective and safe in reducing the LDL-C levels and leading to plaque regression/stabilization in Japanese patients.